Racial Discrimination, Cultural Processes, and Mental Health Among Individuals from Asian Backgrounds during COVID-19: A Narrative Review - Rodriguez, Cloudia; Feng, Ruo Ying; Campbell, Zoe; Poitras, Marilou; Vitoroulis, Irene (University of Ottawa Journal of Medicine, 2022)
Purpose: The goal of this paper is to examine racial/ethnic discrimination among young adults from Asian backgrounds, the extent to which these experiences affect their mental health, and whether cultural processes and coping strategies mitigate the impact of discrimination on mental health. Background: Due to the Coronavirus (COVID-19) originating from Wuhan, China, there has been an increase in discrimination and xenophobia directed towards Asians worldwide, most prominently in Western countries. Fear of experiencing discrimination can harm mental health. Perceptions of discrimination and ways of coping with it may be influenced by cultural processes, such as acculturation and coping strategies. For young people, the consequences of negative bias towards one’s group, in addition to facing COVID-19-related stressors, could be harmful to mental health. Objectives: Racial/ethnic discrimination experienced among Asians living in Canada within the COVID-19 context and potential cultural processes (acculturation orientation, coping strategies) that might reduce the impact of discrimination on mental health. Methods: Articles on the impact of COVID-19 on mental health and racial/ethnic discrimination concerning the pandemic within the North American context were reviewed to examine the extent to which ethnocultural factors were addressed in the recent literature. Within the COVID-19 context, the discrimination experiences and well-being of young adults aged 17-25 years old were examined. To investigate whether cultural processes are associated with perceptions of racial/ethnic discrimination, related topics such as coping strategies, acculturation orientation, and physical health, earlier articles were sought out, with a primary focus on Canada and the US. Keywords searched on Google Scholar, PsychINFO, and PubMed databases included Asian and Chinese racial/ethnic discrimination, COVID-19, Canada, coping with stressors, and Asian acculturation. Research on COVID-19 was examined from 2019 onward, while acculturation, coping, and discrimination articles from 1999 to 2021 were considered. Discussion: Since the emergence of the COVID-19 pandemic, there has been a decline in mental health worldwide. Select groups, notably those from low SES backgrounds, youth, and people from Asian backgrounds have been affected more strongly than the general population. Low SES groups have faced poorer health outcomes due to limited resources. Individuals from Asian backgrounds have been targets of xenophobic attacks, being blamed for the Coronavirus and accused of spreading it in the Western context. During this time, young adults have also experienced a massive shift in their daily routine of school and socializing, increasing their isolation and thereby affecting their mental health. To cope with the stressors, a variety of strategies have been used, such as social support and exercise. These strategies may play a particularly adaptive role in the mental health of people at risk of experiencing ethnic discrimination Conclusion: The COVID-19 pandemic has had a negative impact on young adults’ mental health due to social isolation and changes in daily routines. Most research on Asians in North America has been from the US with limited findings from Canadian samples. Findings regarding the specific mental health impacts that COVID-19 has had on individuals from Asian backgrounds, the stigma and ethnic discrimination they are facing, their coping mechanisms, and their mental health in Canada are currently limited. This dual threat for Asian young adults makes them particularly vulnerable in the context of the current pandemic. Keywords: COVID-19, Asian young adults, xenophobia, racial discrimination, acculturation, coping